Teaching and human competencies necessary for the integrated education teaching staff from the perspective of directors and families in the primary education sector at the regional directorate of Inezgane Ait Melloul: . - ABBOU, ALI AIT (Journal of Curriculum and Teaching Methodology, 2024)
This study investigated the requisite professional competencies for educators engaged in inclusive primary education, as perceived by principals of inclusive educational institutions and families of learners. It employs analytical descriptive methodology, focusing on vocational competencies, inclusive education, primary education, and integrated educational institutions. The sample comprises principals and families of learners with intellectual disabilities, selected through a caste-random approach. Data collection involved surveys and interviews, with analysis conducted using SPSS. Findings indicate high perceived competency levels among faculty members, as reported by principals, while families perceive competency levels as moderate. However, both groups perceive a high degree of inclusive education practice among faculty members. No statistically significant differences were found based on years of integration work or scientific qualification. Recommendations include intensifying continuous training for faculty members and exploring additional topics to enhance professional skills in integrated education at the primary level.